Exploring Differences in Learning Interest Between First-Year and Second-Year Undergraduate Students - Putri, Aulia Asyifani; Julius, Andre; Widiawati, Widiawati; Thahir, Muthahharah (Research Collaboration Community (Rescollacom), 2025)
This study aims to explore the differences in learning interest between first-year and second-year undergraduate students in a higher education context. Learning interest is a crucial component of student engagement, encompassing emotional responses, attention, participation, and intrinsic motivation. The research employed a quantitative approach using a descriptive comparative design. A total of 301 students from Universitas Ma’soem were selected as respondents through stratified proportional random sampling. Data were collected using a validated questionnaire based on four indicators of student interest and analyzed using JASP software. Descriptive analysis revealed that second-year students demonstrated higher levels of learning interest (M = 93.558, SD = 8.809) compared to first-year students (M = 90.844, SD = 7.572). The data for both groups were normally distributed, as confirmed by the Shapiro–Wilk test. The assumption of homogeneity of variances was met based on Levene’s Test. Further inferential analysis using one-way ANOVA indicated a significant difference in learning interest between the two groups, with F(1,299) = 8.238 and p = 0.004. The findings suggest that students’ learning interest tends to increase as they progress academically, likely due to greater familiarity with learning environments, improved self-regulation, and stronger academic identity. These results imply the need for tailored instructional strategies that consider students’ academic stage. Early interventions for first-year students may be essential to foster engagement, while more complex, autonomous learning experiences may be appropriate for second-year students. This study contributes to a deeper understanding of student engagement dynamics across different academic levels in higher education.